南硫黄島のネズミ類調査(<特集>南硫黄2007) - 川上 和人; 鈴木 創 (首都大学東京小笠原研究委員会, 2008)
小笠原諸島では、移入種であるクマネズミが無人島も含めて広く分布している。本種は、動植物の捕食者として生態系に大きな影響を与えることが知られており、保全上の懸案事項の一つとなっている。南硫黄島では、これまでネズミ類の侵入は確認されていないが、前回調査が行われた1982年以後に侵入している可能性は否定できない。そこで、南硫黄島においてネズミ類の侵入の有無を明らかにするため、誘引餌の設置、自動撮影調査、食痕の確認等を行った。この結果、ネズミ類が生息しているという証拠は得られず、現在のところ南硫黄島にはネズミ類が生息していないと考えられた。ネズミ類が生態系へ与える影響は極めて大きいため、今後もネズミ類の侵入に関してはモニタリングを続ける必要がある。 The black rat Rattus rattus is widely distributed in the Bonin Islands, including uninhabited islands. The black rat is of great concern for conservation of the islands because it can intensively impact the native biota as a predator. To date, rats and mice have never been reported on Minami-Iwo-To Island. However, rats may have invaded since the last survey in 1982. To confirm the absence of rats on Minami-Iwo-To Island, we used attractant baits to conduct a camera trap survey and checked for rats in the field. We found no evidence of rats on the island and suggest that rats and mice remain absent. Because rats can swim, they may still accidentally invade; therefore, regular monitoring should be conducted.